PENGEMBANGAN KOMIK DIGITAL BERMUATAN KARAKTER GOTONG ROYONG BERBASIS KEARIFAN LOKAL SASAK ‘BEGAWE BELEQ’ UNTUK SISWA KELAS IV SEKOLAH DASAR - Aulya Nurani; Sudirman; Moh. Irawan Zain; Muhammad Tahir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to produce a design and determine the practicality of digital comicswith gotong royong character based on local sasak ‘begawe beleq’ for grade IVelementary school students. The type of research used is development research(Research and Development) with the ADDIE model which consists of five stages,namely Analysis, Design, Development, Implementation, and Evaluation. Thisresearch was conducted at SDN 27 Cakranegara with the research subjects beinggrade IV students. Data collection techniques used questionnaires anddocumentation. The instruments used were validation sheets by media experts,material and language experts, as well as teacher and student responsequestionnaires. The results showed that digital comics with gotong royong characterbased on Sasak local wisdom ‘Begawe Beleq’ obtained a media expert validationscore of 96.6%, material expert validation of 91.3% and linguists 90% which wereincluded in the very valid category. The small group trial showed a level ofpracticality of 93.2% based on student responses and 96% based on the responsesof class IV teachers. In the large group trial, the level of practicality based on studentresponses reached 91.2%, while the grade III teacher was 98%, the practitionerteacher (librarian) obtained a score of 98% and the grade IV teacher 98% aftermaking improvements according to the input in the small group trial. All the scoreswere in the very practical category. So it can be concluded that digital comics withgotong royong character based on Sasak local wisdom ‘Begawe Beleq’ are veryvalid and practical for use in grade IV elementary school students.